ANALYSIS OF NATO'S MILITARY AID TO UKRAINE'S MILITARY POWER IN 2022-2023 - Joel Siburian (UNIDA Gontor, 2024)
This study aims to answer the question of why foreign military aid, especially from NATO, was given to Ukraine during the 2022-2023. Through a qualitative approach and the concept of Foreign Military Aid, this study analyzes the motivations behind such military aid and its impact on Ukraine's military power. Taking into account the role of non-military forces and civilian participation, the study also explores why NATO want to give a hand in foreign military aid for Ukraine who has affected the dynamics of the conflict between Ukraine and Russia. As such, the study provides in-depth insight into the factors driving NATO to provide military assistance to Ukraine in the context of the ongoing conflict in which NATO seeks to maintain NATO's good name and keep stem Russian hegemony in Eastern Europe.